1995
DOI: 10.1074/jbc.270.37.21806
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Divergent Calmodulin Isoform from Soybean Which Has Differential Ability to Activate Calmodulin-dependent Enzymes

Abstract: Calmodulin plays pivotal roles in the transduction of various Ca 2؉-mediated signals and is one of the most highly conserved proteins in eukaryotic cells. In plants, multiple calmodulin isoforms with minor amino acid sequence differences were identified but their functional significances are unknown. To investigate the biological function of calmodulins in the regulation of calmodulin-dependent enzymes, we cloned cDNAs encoding calmodulins in soybean. Among the five cDNAs isolated from soybean, designated as S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
161
0
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(175 citation statements)
references
References 40 publications
7
161
0
7
Order By: Relevance
“…A diversity of Ca 21 sensors, including Ca 21 -dependent protein kinases and calcineurin-like proteins, likely endow plants with a highly specific and complex Ca 21 signaling network (Luan et al, 2002). Consistent with earlier reports (Lee et al, 1995(Lee et al, , 1997Liao et al, 1996), we observed a differential response of native NADK activity to a variety of CaM-related proteins, including seven that had not previously been cloned or studied. Interestingly, CML10, which is about 64% identical to the conserved CaM but possesses a unique 42-residue Figure 6.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A diversity of Ca 21 sensors, including Ca 21 -dependent protein kinases and calcineurin-like proteins, likely endow plants with a highly specific and complex Ca 21 signaling network (Luan et al, 2002). Consistent with earlier reports (Lee et al, 1995(Lee et al, , 1997Liao et al, 1996), we observed a differential response of native NADK activity to a variety of CaM-related proteins, including seven that had not previously been cloned or studied. Interestingly, CML10, which is about 64% identical to the conserved CaM but possesses a unique 42-residue Figure 6.…”
Section: Discussionsupporting
confidence: 80%
“…Effect of Various CaM-Related Proteins on Native NADK Activity Previous studies on pea (Pisum sativum) NADK have demonstrated a differential response of the enzyme to various CMLs unique to plants (Lee et al, 1995(Lee et al, , 1997Liao et al, 1996). We examined the responsiveness of Arabidopsis native NADK to seven novel Arabidopsis CML recombinant proteins and a previously described protein, CML10 (originally termed CaBP-22; Ling and Zielinski, 1993).…”
Section: Characterization Of Recombinant and Native Nadk Activity Andmentioning
confidence: 99%
“…The vanadate-sensitive ATPase activities of vector control (triangles), SCA1p (squares), SCA1p nt52 (diamonds), and SCA1p nt85 (circles) were determined at 5 M free [Ca 2ϩ ]. The concentration of soybean calmodulin isoform 1 (SCaM-1; Lee et al, 1995) was varied from 0 to 100 nM. Data shown are the average of three independent experiments.…”
Section: Constructsmentioning
confidence: 99%
“…Isolation of total RNA and RNA gel blot hybridization were performed as described (Lee et al, 1995). SB-P cell culture was maintained in KN-1 medium as described (Horn et al, 1989).…”
Section: Rna Gel Blot Analysesmentioning
confidence: 99%
“…Calmodulin was purified from bovine brain as described with a few modifications (Gopalakrishna and Anderson, 1982;Lee et al, 1995) from 350 g of bovine brain. The homogenate of rat brain (SD) was prepared by Warring blender and Potter-Elvehjem homogenizer in one volume of 30 mM Hepes, pH 7.4, 2 mM EDTA, 2 mM EGTA, 1 mM CaCl 2 , 1 mM DTT, 1 mM PMSF, 4 µg/ml aprotinin, 2 µg/ml leupeptin.…”
Section: Purification Of Cammentioning
confidence: 99%